Investigating the biochemical association of gestational diabetes mellitus with dyslipidemia and hemoglobin - Akash, Muhammad Sajid Hamid; Noureen, Sibgha; Rehman, Kanwal; Nadeem, Ahmed; Khan, Mohsin Abbas (Frontiers in Medicine, 2023)
Aims: To investigate the biochemical correlation of hemoglobin (Hb), dyslipidemia, and HbA1c with gestational diabetes mellitus (GDM).Background: GDM is a condition that develops during pregnancy and is characterized by high blood sugar levels. Biochemical parameters such as hemoglobin (Hb), dyslipidemia, and HbA1c have been implicated in the development of GDM. Understanding the correlation between these biochemical parameters and GDM can provide insights into the underlying mechanisms and potential diagnostic markers for the condition.The objective of this study was to evaluate the correlation of various biochemical parameters, including Hb, dyslipidemia, and HbA1c, in pregnant women with and without GDM.A cross-sectional study design was used. Pregnant females attending a tertiary care hospital in Faisalabad between September 1 st , 2021, and June 25 th , 2022, were included in the study. The participants were divided into two groups: those with GDM (GDM group) and those without GDM (non-GDM group). Blood glucose, Hb, and lipid levels were compared between the two groups using statistical tests, including chi-square, independent sample t-test, and Pearson's correlation.Result: Out of the 500 participants, 261 were in the 2nd trimester and 239 in the 3rd trimester.Maternal age showed a significant difference between the GDM and non-GDM groups. The levels of Hb, TC, HDL, LDL, and HbA1c significantly differed (P < 0.05) between the two groups. TC (r = 0.397), TG (r = 0.290), and LDL (r = 0.509) showed a statistically significant and moderately positive correlation with GDM. HDL (r = -0.394) and Hb (r = -0.294) showed a moderate negative correlation with GDM.Increased levels of HbA1c, TC, and LDL, along with decreased levels of HDL and Hb, were identified as contributing factors to GDM. The levels of TC, TG, and LDL were positively correlated with GDM, while HDL and Hb were negatively correlated. The findings of this study suggest that monitoring and managing hemoglobin, dyslipidemia, and HbA1c levels during pregnancy may be important in identifying and potentially preventing or managing GDM. Further research is needed to explore the underlying mechanisms and potential interventions targeting these biochemical parameters in relation to GDM.